Water Resources for Florida Citrus - Brian Boman; Larry Parsons (EDIS, 2002)
This is document No. CH162 and Circular 1420, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2002.